Pengaruh Pelatihan Dan Pengawasan Terhadap Produktivitas Rumah Tangga Sasaran Pada BUMDesa Sejahtera Desa Dringu Kaupaten Probolinggo - Lia Sari Devi; Abd Kodir Djaelani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT This study aims to determine the effect of training and supervision partially or simultaneously using statistical tests with the help of SPSS version 25. The population in this study was 142 members with a sample of 59 target household members by distributing questionnaires to obtain data. The analysis tools used in this study are the instrument test, normality test, classic assumptions, multiple linear regression analysis, and hypothesis testing. With the results of the analysis showing that training has a positive effect on productivity, while supervision has no effect on the productivity of the target household. Simultaneously training and supervision affect the productivity of target households BUMDesa Sejahtera Customs Village. Keywords: Training, Supervision, Productivity